Does Distributed Leadership Deliver on Its Promises in Schools? Implications for Teachers' Work Satisfaction and Self-Efficacy - Mihai Tucaliuc; Petru Lucian Curșeu; Arcadius Florin Muntean (MDPI AG, 2023)
Although surrounded by theoretical confusion and methodological ambiguity, distributed leadership has been acclaimed as beneficial for teacher performance and student achievement. We set out to explore organizational identification and empowerment as two mechanisms that explain the positive and negative association between distributed leadership and teacher work-related outcomes. We build on social identity, social interdependence and cognitive schema theories to argue that teachers' cognitive dysfunctional schema of distrust and dependence moderate the association between distributed leadership on the one hand and organizational identification and empowerment on the other hand. We used multilevel mediation analyses to test our hypotheses in a sample of 3528 teachers, nested in 329 Romanian schools and our overall results reveal a negative association between distributed leadership and empowerment as well as organizational identification. Distrust cognitive schema accentuate the negative association between distributed leadership and empowerment, while dependence schema accentuate the negative association between distributed leadership and organizational identification. Finally, organizational identification mediates the association between distributed leadership and teachers' work self-efficacy as well as satisfaction, while empowerment only mediates the association between distributed leadership and work satisfaction.